DESIGN AND DEVELOPMENT OF RECRUITMENT APPLICATION AND SELECTION OF EMPLOYEES BASED ON COMPETENCE IN RSIA PUTRI SURABAYA - Mirza, Kamanda Satio; Maulana, Yoppy Mirza; Sunarto, M.J Dewiyani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Putri Hospital Surabaya is a company or institution that specializes in health especially in pregnant and childbirth care that rescue at Arief Rahman Hakim Street, Surabaya. In its business process Putri Hospital has the employee resource needs of approximately 179 employees divided into 21 sections. In fulfilling the needs of these employees and apply one mission of RSIA Putri Surabaya is